What do immigrants value most about Switzerland? Evidence of the relative importance of income taxes - Mario Morger (Center for Economic Studies and ifo Institute (CESifo), 2013)
This study investigates whether migrants, once they have decided to move to Switzerland, prefer to settle in municipalities that feature low income taxes. In line with the existing literature, results from cluster-specific count data models indicate that income taxes are a significant pull factor for international migration decisions. The same is true with respect to intra-national migration. However, dominance analysis suggests that the relative impact of taxes compared to other locational factors is rather low. Urbanity characteristics, labor-market, and network effects are by far the most important factors to influence the choice of destination municipality.
Keywords: H24; H73; J61; R23; 330; migration; tax competition; dominance analysis; relative importance